The Legal Vacuum and Normative Conflicts in Bankruptcy Applications by Workers - Ougy Dayyantara; Zudan Arief Fakrulloh (PT. Publikasiku Academic Solution, 2024)
This study investigates the legal issues arising from Supreme Court Circular Letter Number 2 of 2019 concerning bankruptcy applications by workers, focusing on the legal vacuum and lack of clarity regarding the rights that can form the basis of such applications. The research employs a normative legal method, analyzing legal norms, legislation, and judicial decisions to assess the challenges faced by workers in filing bankruptcy applications. The findings reveal significant gaps, including the requirement for a legally binding decision from the Industrial Relations Court (PHI) prior to filing, which creates procedural delays and confusion. The lack of clarity on the scope of workers' rights, especially regarding non-wage entitlements such as bonuses and allowances, further exacerbates legal uncertainty. The study recommends revising the circular to address these gaps, enhancing coordination between PHI and the Commercial Court, and improving legal awareness among workers. These steps aim to create a more robust framework for protecting workers' rights and ensuring legal certainty in bankruptcy applications. The study highlights the urgent need for reform to strengthen legal protections for workers in Indonesia.